(untitled) (Scientific journal of the Fergana State University, 2025)
The article is devoted to the study of the relationship between axiology and language, focusing on the expression of values through phraseological units such as idioms and metaphors. Language is considered not only as a means of communication but also as a mirror reflecting the cultural, ethical, and historical features of society. Special attention is paid to the analysis of idiomatic expressions from different cultures, which allows us to identify differences in priorities, norms, and worldviews. Phraseology plays a key role in language study, as it reflects the profound cultural and value aspects of society. Phraseological units are not just stable expressions but also carriers of collective experience, traditions, and worldviews. The study of phraseology fosters intercultural dialogue by helping to identify commonalities and unique characteristics of various ethnic groups. Methods of comparative analysis, conceptual metaphor analysis, and interpretation of phraseological units were applied. The research demonstrates how language serves as an important tool for preserving cultural values, and traditions, and transmitting historical experience. Additionally, the role of language in maintaining gender stereotypes and the possibilities for overcoming them are examined. The results highlight that language is not only a means of transmitting values but also a powerful tool for changing them. In conclusion, the importance of studying language as a tool for intercultural empathy, promoting inclusive communication, equality, and deep understanding of diverse cultural traditions is emphasized.